Modified ovarian response prediction index: a novel index for ovarian response prediction in GnRH agonist cycles - Kalpana, B.; Panda, Soumya Ranjan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Evaluation of the ovarian reserve is necessary to achieve an appropriate controlled ovarian stimulation (COS). This can be done by correctly predicting the ovarian response. The objective of this study was to derive a simple index by combining the above parameters which will be helpful determining ovarian response. Methods: This retrospective analysis was performed at Guru hospital, Madurai, involving 162 patients between July 2016 and July 2018. Inclusion criteria was all patients attending for their first ICSI (intracytoplasmic sperm injection) cycle between the above period, GnRH agonist protocol as the method of ovarian stimulation, no history of any previous ovarian surgery, presence of both ovaries and no evidence of any obvious endocrine disorders. We calculated MORPI values by multiplying the AMH (ng/ml) level by the number of antral follicles (2-9 mm), and the result was divided by the age (years) of the patient and the day- 3 serum FSH level. Results: At a cut-off value of 35 (AUC-0.952) for collection of ≥ 4 oocytes and 140 (AUC-0.952) for collection of ≥ 15 oocytes, MORPI was found to have optimum sensitivity and specificity under ROC curve analysis. Conclusions: MORPI is a simple, precise and cost effective index to predict a low ovarian response, the collection of >4 MII oocytes and an excessive ovarian response in infertile women. This index also has a good ability to predict the clinical pregnancy rate. This might be used to improve the cost-benefit ratio of ovarian stimulation regimens.